2022
DOI: 10.3389/fcimb.2022.1039197
|View full text |Cite
|
Sign up to set email alerts
|

Epitope profiling of monoclonal antibodies to the immunodominant antigen BmGPI12 of the human pathogen Babesia microti

Abstract: The significant rise in the number of tick-borne diseases represents a major threat to public health worldwide. One such emerging disease is human babesiosis, which is caused by several protozoan parasites of the Babesia genus of which B. microti is responsible for most clinical cases reported to date. Recent studies have shown that during its intraerythrocytic life cycle, B. microti exports several antigens into the mammalian host using a novel vesicular-mediated secretion mechanism. One of these secreted pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Immunodetection of BdV234 and BdV38--Polyclonal antibodies raised in rabbits (Cocalico Biologicals, Inc., PA) against the indicated B. duncani proteins were purified and used for the immunodetection analysis as described in detail (32). Briefly, supernatant (S), hemolysate (H), and parasite pellet (P) fractions collected either from B. duncani in vitro culture in hRBC (18% parasitemia) or B. duncani infected (24% parasitemia) or uninfected mRBCs were mixed with 4X Laemmli sample buffer (3:1 ratio), boiled at 80°C for 5 min and separated on 4-20% Mini-protean gels (Bio-Rad, P4568093).…”
Section: Isolation Of Extracellular Vesicles From Plasma Culture Supe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunodetection of BdV234 and BdV38--Polyclonal antibodies raised in rabbits (Cocalico Biologicals, Inc., PA) against the indicated B. duncani proteins were purified and used for the immunodetection analysis as described in detail (32). Briefly, supernatant (S), hemolysate (H), and parasite pellet (P) fractions collected either from B. duncani in vitro culture in hRBC (18% parasitemia) or B. duncani infected (24% parasitemia) or uninfected mRBCs were mixed with 4X Laemmli sample buffer (3:1 ratio), boiled at 80°C for 5 min and separated on 4-20% Mini-protean gels (Bio-Rad, P4568093).…”
Section: Isolation Of Extracellular Vesicles From Plasma Culture Supe...mentioning
confidence: 99%
“…Immunofluorescence assay (IFA)--Immunofluorescence assay was performed as reported previously (30,32) and described briefly in the supplementary methods.…”
Section: Isolation Of Extracellular Vesicles From Plasma Culture Supe...mentioning
confidence: 99%
“…Human babesiosis is a newly recognized tick-borne infection that is caused by an intraerythrocytic protozoan species belonging to the genus Babesia ( Chand et al, 2022 ). In recent decades, the epidemiology of human babesiosis has shifted from a few isolated cases to the emergence of outbreaks in the northeastern and midwestern United States, and research has shown that human babesiosis develops within the red blood cells of humans and small rodents ( Tanowitz and Weiss, 2009 ).…”
Section: Introductionmentioning
confidence: 99%